PENGGUNAAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP KEMAMPUAN KOGNITIF PESERTA DIDIK PADA MATA PELAJARAN IPAS KELAS IV SEKOLAH DASAR - Deny Apriyani Juhri; Selly Prasasti; Khoirunisa Zahrani; Wahyu Aulia Rahmadila; Rahmat Elvendi (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2025)
ABSTRACT The inadequate cognitive abilities of students in the IPAS subject indicate the need for a more appropriate learning model. The Contextual Teaching and Learning (CTL) model is expected to improve students’ understanding through active engagement and by connecting the material to everyday life contexts. This study aims to analyze the influence of implementing the Contextual Teaching and Learning (CTL) model on the cognitive abilities of fourth-grade students in the Natural and Social Sciences (IPAS) subject. This research employed a quantitative method with a Pre-Experimental One Group Pretest–Posttest Design. The sample consisted of all fourth-grade students of UPT SDN 1 Pringsewu Selatan, totaling 30 students, comprising 16 female and 14 male students. The research data were collected using multiple-choice tests developed according to the indicators of cognitive abilities (C1–C6). The validity test results showed that 10 items were valid with an r count > r table (0.444), while the instrument’s reliability, calculated using the KR-20 formula, yielded a value of 0.806, categorized as high. The prerequisite tests indicated that the data were normally distributed and homogeneous. The t-test produced a value of t count = 16.001 > t table = 2.080, leading to the conclusion that the use of the CTL model had a significant effect on students’ cognitive abilities. Thus, the application of the Contextual Teaching and Learning model proved effective in improving students’ cognitive abilities in IPAS learning through active engagement, learning activities linked to real-life contexts, and more meaningful learning experiences. ABSTRAK Kondisi kemampuan kognitif siswa yang belum memadai pada mata pelajaran IPAS menunjukkan kebutuhan akan penerapan model pembelajaran yang lebih tepat. Model Contextual Teaching and Learning (CTL) diharapkan dapat meningkatkan pemahaman siswa melalui keterlibatan aktif dan pengaitan materi dengan konteks kehidupan sehari-hari. Penelitian untuk menganalisis pengaruh penerapan model pembelajaran Contextual Teaching and Learning (CTL) terhadap kemampuan kognitif peserta didik pada mata pelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) kelas IV Sekolah Dasar. Penelitian ini menggunakan metode kuantitatif dengan rancangan Pre-Experimental One Group Pretest-Posttest Design. Sampel dalam penelitian ini mencakup seluruh peserta didik kelas IV UPT SDN 1 Pringsewu Selatan yang berjumlah 30 orang, terdiri dari 16 siswa perempuan dan 14 siswa laki-laki. Data penelitian dikumpulkan menggunakan tes pilihan ganda yang dikembangkan sesuai dengan indikator kemampuan kognitif (C1–C6). Hasil uji validitas menunjukkan 10 butir soal valid dengan nilai r hitung > r tabel (0,444), sedangkan reliabilitas instrumen menggunakan rumus KR-20 menghasilkan nilai 0,806 dengan kategori tinggi. Hasil uji prasyarat menunjukkan bahwa data memiliki distribusi yang normal serta bersifat homogen. Uji-t menghasilkan nilai nilai t hitung = 16,001 > t tabel = 2,080, sehingga dapat disimpulkan bahwa penggunaan model CTL berpengaruh signifikan terhadap kemampuan kognitif peserta didik. Dengan demikian, penerapan model Contextual Teaching and Learning terbukti mampu meningkatkan kemampuan kognitif peserta didik dalam pembelajaran IPAS melalui keterlibatan aktif, aktivitas belajar yang dikaitkan dengan konteks nyata, serta pengalaman belajar yang lebih bermakna.